Analisis Strategi Bertahan Usaha Kelompok Tani Kopi di Tengah Pandemi Covid-19: Studi Kasus Kelompok Tani Binaan koperasi Buana Mandiri - Dinda Delfi Permata Rambe; Fauzi Arif Lubis; Atika Atika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2022)
This study aims to determine the survival strategy applied by the coffee farmer groups assisted by the Buana Mandiri cooperative in the midst of the covid-19 pandemic. The research method used is to use a descriptive descriptive qualitative methods of SWOT analysis. The results showed that the farmer groups assisted by the Buana Mandiri Cooperative did additional work and took advantage of the time apart from growing coffee by planting other crops. Based on the results of research using SWOT analysis, it was found that the farmer groups assisted by the Buana Mandiri Cooperative are in Quadrant I.. Under these conditions, the strategy that must be carried out is to support an aggressive growth policy (Growth Oriented Strategy), meaning that farmer groups are in prime condition so that it is very possible to continue to expand, achieve maximum progress, and increase growth. Keywords: Devensive Strategy, Coffe Farmer Groups, Covid-19 Pandemic, SWOT Analysys